THE PROSPECTS OF ADMINISTRATION AND ACCOUNTING IN RUSSIA: VECTORS OF DEVELOPMENT OF CIVIL LEGISLATION - AIUSHEEVA, IRINA ZORIKTUEVNA; SOYFER, TATIANA VLADIMIROVNA (Revista Gestão Organizacional, 2022)
Purpose: The process of digitalization changes strategies for social intercourse organization, it predetermines the emergence of disruptive technologies and trends such as sharing economy that plays a special part in the sphere of management. The purpose of the given research is to shape developments of civil legislation, which will facilitate the legal framing of adequate mechanisms of civil regulation of relations in the sphere of shared use of goods and services (sharing economy) under the growth of digital technologies. Method / approach: The research reviews and analyses basic ideas of economic and legal sciences. It studies empiric material such as sample contracts and cases of judicial practice. The main research methods were deduction (specification of general principles and their application to particular spheres), induction (the study of work arrangement of certain platforms under sharing economy and further specification of general principles), and comparative law method. Main Findings: Sharing economy activities may be diverse. It can be of profit-seeking or non-profit character. Thus, relations under discussion can be mediated by gratuitous and non-gratuitous contracts. Participants of sharing economy can be considered commercial and non-commercial organizations, citizens, and civil communities that are not legal entities. It results in the necessity of solving the problem of their legal standing to take part in civil transactions. Methodological / social / managerial contributions: Research findings are important for developing legal science and civil law in particular. Based on the conducted research, the authors determine the main vectors of development of civil legislation to ensure the evolution of sharing economy and management in Russia; therefore, obtained results can be applied in lawmaking, law enforcement activities, the teaching profession, and research in the sphere of legal science. Originality / relevance: In Russia relations existing within the sharing economy sector have not got suitable legislative support yet as some of them lie outside the legal environment, so it creates a lot of disputable problems in real life. In this study, for the first time, an attempt was made to reveal and examine special aspects of emerging relations for their proper legal regulation.